THU0405 Assessment of the Implementation of the Revised Recommendations for Screening of Hydroxychloroquine Retinopathy in the Clinical Practice of Opthalmologists and Rheumatologists. (9th June 2015) - Wollman, J.; Shulman, S.; Brikman, S.; Padova, H.; Elkayam, O.; Paran, D.
Abstract : Background: The American Academy of Ophthalmology published in 2011 revised recommendations regarding screening for hydroxychloroquine (HCQ) toxicity. Little is known about the implementation of these guidelines in clinical practice Objectives: The aim of this study was to assess the implementation of these recommendations by rheumatologists and ophthalmologists in Israel Methods: A questionnaire was developed, consisting of 13 questions pertaining to each physician's routine practice in the follow up of patients treated with HCQ. The questionnaire was distributed among all members of the Israeli societies of Rheumatology and Ophthalmology as a web survey. The study was conducted for a period of 6 months (May to November 2014). Results: One hundred and twenty one physicians responded to the questionnaire, 49 rheumatologists and 71 ophthalmologists. Sixty three percent of the rheumatologists prescribed a HCQ dose of not more than 6.5mg/kg and not more than 400mg/d while only 17 ophthlamologists responded to this question of whom only 4 were aware of the dose recommendations. Sixty nine percent of all the responders followed patients treated with HCQ for more than 5 years, 12.4% followed patients on treatment for more than 10 yrs. Only 82.6% recommend a baseline ophthlamologic examination at baseline while 7.4% recommend baseline evaluation only for patients at risk. Forty two percent of all responders postpone initiation of HCQ treatment until completion of a baseline evaluation. Only 0.6% of the rheumatologists and 19% of the ophthalomologists were aware of the recommended ophthalmologic assessments for baseline and follow up evaluation. Thirty percent of the responders recommend red on white visual field (VF) assessment and 14% recommend 24-2 VF, while a similar percentage recommend these tests for follow up (33%, 13% respectively). HCQ treatment was discontinued due to abnormal findings in the following tests: red on white VF:19%, 24-2 VF: 7%, fundoscopic findings: 25%, color field: 5%, OCT: 19% and auto-fluorescence: 3%. When an abnormal test was detected 56% recommended cessation of therapy while 23% recommended additional evaluation before treatment arrest. Only 14% of the responders recommend first follow up evaluation after 5 years for patients without risk factors and the remainder recommend more frequent testing. Similarly, 56.2% recommend yearly follow up while the remainder recommend more frequent evaluation. Eighty three percent of the responders were not aware of all of the known risk factors for HCQ toxicity. Conclusions: Many physicians in Israel are unaware of the 2011 recommendations regarding baseline and follow up tests, timing of assessments, drug discontinuation strategy and risk factors to be considered regarding HCQ retinal toxicity. Use of inappropriate tests to detect HCQ retinal toxicity may lead to unnecessary cessation of beneficial HCQ treatment while lack of consideration of risk factors may pose patients at risk for toxicity. These results emphasize the importance of implementing the 2011 recommendations for better monitoring of patients using HCQ. References: Ophthalmology 2011;118(2):415-422 Disclosure of Interest: None declared